2019
DOI: 10.3390/ijerph16224471
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture Feeds Can Be Outlaws for Eutrophication When Hidden in Rice Fields? A Case Study in Qianjiang, China

Abstract: Water eutrophication caused by agricultural production has become one of the most important factors that impede sustainable rural environmental governance in China. As a result, the Chinese central and local governments want to reduce the use of nitrogen and phosphorus fertilizer and gain socioeconomical profit simultaneously by promoting crayfish and rice integrated system (CRIS) in the rural areas with abundant water resources. In this article, we investigated whether CRIS in Qianjiang, Hubei, the origin pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 33 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Fertilizer improves soil fertility significantly, and the continuous input of feed also increases nutrient elements in the sediment (Liang et al 2013 ; Liu et al 2019a ). Our study found that TN, TP, AP and AN in paddy soil and ditch sediment increased compared with the initial stage under the rice-crab co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Fertilizer improves soil fertility significantly, and the continuous input of feed also increases nutrient elements in the sediment (Liang et al 2013 ; Liu et al 2019a ). Our study found that TN, TP, AP and AN in paddy soil and ditch sediment increased compared with the initial stage under the rice-crab co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…48 The implementation of feeding practices can enhance fish production without negatively impacting rice yield, and the consistent provision of fish feed also results in the accumulation of nutrients in the ditch bottom soil. 4,49 In the present study, we found that S75 treatment significantly increased rice yield and reduced fish yield compared with S0, S25 and S50 treatments, whereas S0 and S25 treatments significantly reduced rice yield and increased fish yield compared with S50 and S75 treatments, respectively (Table 1), suggesting that inadequate basal fertilizer tends to affect rice yield, whereas overuse of the fish feed and basal organic fertilizer also causes the accumulation of nutrients in the ditch bottom (Figs 1 and 2). Ayub et al 50 also reported that chicken manure can increase the organic matter content of the pond bottom soil.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, freshwater crayfish (Procambarus clarkii) and rice (Oryza sativa) were selected for co-culture in this study. The experiment plot was divided into a small area, with 20 m (L) × 12 m (W), and rice cultivation occupied about 60% of the total area of the plot; the depth of the ditch was 1.0 m. Rice was transplanted in May and harvested in October [16].…”
Section: Study Area and Experiments Designmentioning
confidence: 99%